Validity and Reliability of a Food Frequency Questionnaire to Assess Habitual Dietary Intake in Northern Vietnam - Van Dinh, T.; Van Dong, H.; Nguyen, Thanh Chung; Lee, Andy (Vietnam Public Health Association, 2013)
The two main objectives of this study were (1) to investigate the face and content validity, and test-retest reliability of a modified food frequency questionnaire (FFQ) originally developed in South Vietnam, and (2) to effectively quantify and monitor habitual dietary intake for the Northern Vietnamese population. Seventy community-dwelling adults were recruited from four provinces in the North Vietnam by convenience sampling. An “experience-based” approach involving 20 focus group participants was adopted to modify the existing instrument. The revised FFQ was then piloted among 20 adults. Test-retest reliability was assessed by face to face interviewing another group of 30 adults twice with an interval of 21 days using the piloted FFQ. The final questionnaire contained 128 food and beverage items after modifications and refinement based on the qualitative data obtained. Face validity and content validity were confirmed by the pilot test. Reasonable reproducibility between repeated administrations of the FFQ was also evident, with intra-class correlations ranging from 0.15 to 0.83 for 15 main food groups. The modified FFQ appeared to be a suitable instrument to evaluate habitual dietary intake of adults in the North Vietnam.